Electrochemical Methods of Transference Number Determination for Polymer Electrolyte Systems: A Comparative Study. Issue 11 (1st November 2022) - Bublil, Shaul; Peta, Gayathri; Fayena-Greenstein, Miryam; Alon-Yehezkel, Hadas; Raskin, Ortal; Elias, Yuval; Aurbach, Doron
Abstract : The transference number for cations, t +, is one of the most important parameters for characterizing polymeric and/or composite solid electrolytes. It expresses the contribution of the positive charge carriers to the total conductivity, which in turn reflects the degree of polarization due to the negative carriers in the electrolyte systems. Four electrochemical methods based on different equations commonly used for obtaining t + are compared. A series of experiments were conducted with solid polymer electrolytes based on polyethylene oxide with and without TiO2 ceramic additive. Interestingly, the oldest method developed and presented four decades ago, emerges as the most simple, reliable, sensitive, repeatable, and stable option for determining t + values over time.